Nora’s lesion: description of a case - Goloborod’ko, Sergey; Krinichanskаyа Maya; Kotliarova, Victoria (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The article describes a rare case of bizarre parosteal osteochondromatous proliferation (Nora’s lesion) on a finger in three patients, treated by the authors. The aetiology of the disease has not been found out yet. Diagnosis is made on the basis of clinical, radiological and histological examinations. The method of treatment of this lesion is surgical.